Poultry Manure and NPK 15 15 15 Fertilizer Application and their Residual Effect on White Yam (Dioscorearotundata) Storage in the Forest Derived Savanna Ecological Zones of Edo State, Nigeria - Manson, Okojie, Oamhen; Aigbe, Osajiele, Mike; O., Osemwota, I. (Canadian Journal of Agriculture and Crops, 2019)
Field experiments were conducted in Igueben, located in the forest derived savanna ecological zone of Edo state. In 2012 and 2013 cropping seasons to determine the effect of poultry manure, NPK 15 15 15 fertilizer and their combinations on the storage of white yam (Dioscorearotundata). The treatments consisted of four levels of poultry manure, 0,4,8 and 12 tons/ha and three levels of NPK fertilizer 0, 100 and 200kg/ha. The treatments were replicated three times and were fitted into randomized complete block design. The poultry manure was applied by broadcasting 2 weeks before planting while the NPK fertilizer was applied during planting. The tubers were carefully harvested after 7months of planting and stored in a barn. Tubers were observed and determined for duration of dormancy, weight loss and the number of tubers that rotted. Result showed that tuber weight loss and rot increased significantly with high levels of poultry manure NPK fertilizer and their combinations. The period of dormancy reduced as level of treatment increased it was concluded that the application of combination of low rate of chemical fertilizer with poultry manure boost yield and storage of white yam. Consequently a combination of 100kg NPK 15 15 15/ha with 12 tonspm/ha is recommended for yam farmers for good storage in the forest derived savanna ecological zone.